Competência de leitura em alunos surdos inclusos na rede regular de ensino - Luccas, Marcia Regina Zemella [UNIFESP] (2011)
Objective: To evaluate the efficacy of reading in hearing impaired or deaf students included in schools of the local regular education network. Methods: analytical observational study conducted with 35 students with sensorineural hearing loss of varying degree, with and without teaching aids, and 71 age- and series-matched listeners. All subjects underwent the Competence Test of Words Reading-TCLP 1.2, Picture Naming Test by Choice of Words-TFN 1.1 and Competence Test of Sentence Reading-SRT 1.2. Results: The deaf or hearing impaired students included in regular education network obtained different results listener students. In the test of Competence Test of Words Reading-TCLP, listeners obtained an average hit rate of 84.5%, while the deaf students obtained 68.8% of accuracy (p=<0,001). Regarding to the Picture Naming Test by Choice of Words-TFN, following average accuracy was observed: 91.6% for listeners, hearing impaired or deaf, 73%(p=<0,001). As for the Competence Test of Sentence Reading-TCLS, listeners achieved an average of 75.7% and the hearing impaired or deaf, 42.9% (p=<0,001). There was no statistically significant difference between deaf and hearing impaired students who attend the support and follow-up class at inclusion and the hearing impaired or deaf students in regular classes only (p=<0,001). Conclusions: The hearing students showed significant difference in reading competence in the three tests presented compared with deaf or hearing impaired ones. We can assert that the hearing students have a good rating on levels of correlation, while the deaf show regular classification. This result points to a failure in the education of the latter in the regular education network.